Condições associadas ao grau de satisfação com a vida entre a população de idosos - Joia, Luciane Cristina; Ruiz, Tânia [UNESP]; Donalisio, Maria Rita (Revista de Saúde Publica, 2007)
OBJECTIVE: As a result of overall growing population's life expectancy, it has become increasingly important to ensure not only that the elderly have greater longevity but also happiness and life satisfaction. The objective of the study was to describe factors associated with life satisfaction among elderly people.METHODS: Three hundred and sixty-five older persons, selected by means of random stratified proportional sampling, were interviewed in 2003. The instrument used was a combination of Flanagan and Nahas questionnaires and WHOQOL-100. There were added questions concerning physical activity extracted from International Physical Activity Questionnaire, questions regarding reported morbidity and emotional assessment, sociodemographic condition and an open question. The level of life satisfaction was measured using a scale from one to seven by means of visual recognition. Hierarchical logistic regression analysis was performed including life satisfaction as a dependent variable and those included the final questionnaire, in blocks, as independent variables.RESULTS: Most elderly were generally rather satisfied with life as well as with specific aspects. The level of life satisfaction was associated with: comfort at home (OR=11.82; 95% Cl: 3.27; 42.63); appraising leisure as quality of life (OR=3.82; 95% Cl: 2.28; 6.39); waking up feeling well in the morning (OR=2.80; 95% Cl: 1.47; 5.36); not reporting loneliness (OR=2.68; 95% Cl: 1.54; 4.65); having three or more daily meals (OR=2.63; 95% Cl: 1.75; 5.90) and not reporting Diabetes Mellitus (OR-2.63; 95% Cl: 1.3 1; 5.27).CONCLUSIONS: Most elderly in the study were satisfied with life and their satisfaction was associated with situations related to being well and not being diabetic.
Life satisfaction among elderly population in the city of Botucatu, Southern Brazil
Keywords: aged; quality of life; life style; questionnaires